Reassessing the role of phospholipase D in the Arabidopsis wounding response - Bargmann, Bastiaan O. R. (2009)
Plants respond to wounding by means of a multitude of reactions, with the purpose of stifling herbivore assault. Phospholipase D (PLD) has previously been implicated in the wounding response. Arabidopsis (Arabidopsis thaliana) AtPLDa1 has been proposed to be activated in intact cells, and the phosphatidic acid (PA) it produces to serve as a precursor for jasmonic acid (JA) synthesis and to be required for wounding-induced gene expression. Independently, PLD activity has been reported to have a bearing on wounding-induced MAPK activation. However, which PLD isoforms are activated, where this activity takes place (in the wounded or non-wounded cells) and what exactly the consequences are is a question that has not been comprehensively addressed. Here, we show that PLD activity during the wounding response is restricted to the ruptured cells using 32Pi-labelled phospholipid analyses of Arabidopsis pld knock-out mutants and PLD-silenced tomato cell-suspension cultures. plda1 knock-out lines have reduced wounding-induced PA production, and the remainder is completely eliminated in a plda1/d double knock-out line. Surprisingly, wounding-induced protein kinase activation, AtLOX2 gene expression and JA biosynthesis were not affected in these knock-out lines. Moreover, larvae of the Cabbage White butterfly (Pieris rapae) grew equally well on wild-type and the pld knock-out mutants.